2008
DOI: 10.1007/s00464-008-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

Transgastric endoscopic peritoneoscopy does not require decontamination of the stomach in humans

Abstract: There was no clinically significant contamination of the peritoneal cavity from the gastroscope after transgastric endoscopic instrumentation in humans. Transgastric instrumentation does contaminate the abdominal cavity but, the pathogens do not mount a clinically significant response in terms of either the species or the bacterial load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 15 publications
3
43
0
Order By: Relevance
“…Advocates of newer procedures are extremely positive about newer methods but they mainly talk about the cosmetic benefits. (6,8,21) There is definitely increased risk of contaimination when gastric (8,14) approach is used. increased risk of incisional hernia (22) following single-incision LC is a reality rather than a possibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advocates of newer procedures are extremely positive about newer methods but they mainly talk about the cosmetic benefits. (6,8,21) There is definitely increased risk of contaimination when gastric (8,14) approach is used. increased risk of incisional hernia (22) following single-incision LC is a reality rather than a possibility.…”
Section: Resultsmentioning
confidence: 99%
“…(3,4,5) Many studies(about50) are found on these newer methods. (6,7,8) Most studies done over small number of patients. (2) Very few studies included more than 50 patients though a couple of them included a figure around 500.…”
Section: Introductionmentioning
confidence: 99%
“…The transgastric access was deemed easier and safer for the patient than the transcolonic access, especially in view of the stomach decontamination issues [11]. Transecting the stomach and moving to the abdominal cavity was relatively easy.…”
Section: Diagnostic Pure Transgastric Notes In An Intensive Therapy Umentioning
confidence: 99%
“…The trials summarized in Table 2 suggest the rate of infectious complications could be low. Human trials investigating transgastric instrumentation of the peritoneal cavity do report contamination of the peritoneal cavity, but the contamination was found to be clinically insignificant [17,27,28] . Other adverse events including bleeding and pneumothoraces are significant complications in human thoracoscopic procedures [29,30] .…”
Section: Barriers To Clinical Practicementioning
confidence: 99%